Pedagogical Basis for Teaching Students How to Carving in Circles - Axmedov Muxomod-Umar Baxridinovich (Zien Journals, 2022)
The article focuses on the historical development of practical art, especially woodworking, the views of our great-grandfathers on educating young people and teaching craftsmanship, teaching young people the rules of ethics, encouraging them to master the secrets of science, directing them to do rewarding work, and encouraging them to engage in creativity Today, it also outlines the pedagogical basis for organizing these events.
Keywords: education; etiquette; equipment; color